2017
DOI: 10.3389/fphys.2017.00708
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Shear Moduli Changes and Frequency of Alternate Muscle Activity of Plantar Flexor Synergists Induced by Prolonged Low-Level Contraction

Abstract: During prolonged low-level contractions, synergist muscles are activated in an alternating pattern of activity and silence called as alternate muscle activity. Resting muscle stiffness is considered to increase due to muscle fatigue. Thus, we investigated whether the difference in the extent of fatigue of each plantar flexor synergist corresponded to the difference in the frequency of alternate muscle activity between the synergists using muscle shear modulus as an index of muscle stiffness. Nineteen young men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
0
19
1
Order By: Relevance
“…However, our results are in contrast to a previous study (Akagi et al, 2019), which showed an increase in resting VL µ (21.7 ± 32.4%) after a low-intensity prolonged fatiguing task of the KE muscles. Akagi et al (2017) suggested that resting muscle stiffness could be higher after prolonged fatiguing task due to muscle failure to fully relax and cramps. The well-known task dependency of fatigue needs to be considered to better understand discrepancies concerning changes in muscle stiffness and fatigue.…”
Section: Muscle Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results are in contrast to a previous study (Akagi et al, 2019), which showed an increase in resting VL µ (21.7 ± 32.4%) after a low-intensity prolonged fatiguing task of the KE muscles. Akagi et al (2017) suggested that resting muscle stiffness could be higher after prolonged fatiguing task due to muscle failure to fully relax and cramps. The well-known task dependency of fatigue needs to be considered to better understand discrepancies concerning changes in muscle stiffness and fatigue.…”
Section: Muscle Stiffnessmentioning
confidence: 99%
“…Akagi et al (2019) showed an increase in resting VL µ (21.7 ± 32.4%) after a low-intensity prolonged fatiguing task of the KE muscles. Akagi et al (2017) suggested that resting muscle stiffness could be higher after prolonged fatiguing task due to muscle failure to fully relax and cramps. Moreover, it is not known whether the changes in viscoelastic properties of muscles contribute to restoration of force transmission capacities during the recovery period.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] There is no consensus in the literature on the effect of age on muscle stiffness, with some authors reporting increasing and others decreasing muscle stiffness. [38][39][40] A few important factors may be debated regarding this disagreement. First, the difference in the evaluation protocol resulted in varied USE values based on the type of functional muscle assessment.…”
Section: Musclementioning
confidence: 99%
“…The comparison of the obtained numerical results with the experimental response suggested that many modelling assumptions resulted in overestimation of the soft-tissue stiffness. Considering more recent studies focusing on measuring mechanical properties [57][58][59][60][61][62][63][64][65], a lower range of elastic moduli was reported (see Table 2). It is thus important to consider lower values for material parameters that correspond to Although the indentation experiments were used extensively to characterise the in vivo soft tissue behaviours of the lower limb, there were only a few studies that investigated the distributions of stress and strain in the tissue directly beneath the indenter.…”
Section: Discussionmentioning
confidence: 99%